Memahami Perbedaan: Literasi Budaya Sebagai Kunci Menanggulangi Intoleransi Antar Budaya - Sahma Nada Afifah Ekaprasetya; Dinie Anggraeni Dewi; Rizky Saeful Hayat (PT. ALHAFI BERKAH INDONESIA, 2023)
This article discusses the important role of cultural literacy in shaping a global society that is inclusive and responsive to the complexity of an increasingly connected world. Cultural literacy is not only about understanding other people's cultures, but also involves the ability to communicate and adapt in a multicultural environment. The relevance of cultural literacy in a global context can be seen from individual adaptability, understanding of global issues, the formation of extensive social networks, increased cross-cultural cooperation, and understanding of one's own cultural identity. In overcoming intercultural intolerance, cultural literacy has a positive impact, such as reducing stereotypes and prejudice, building empathy, and creating an inclusive environment. Through the conclusion, it is emphasized that cultural literacy is the key to opening the door to a society that is able to celebrate diversity, respond to global challenges, and build a more inclusive world for future generations. This article calls for awareness of the importance of cultural literacy as the main instrument in forming a harmonious and competitive global society.